PENGARUH KEGIATAN LITERASI TERHADAP MINAT BACA WARGA BELAJAR DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM BINTANG FLOBAMORA KOTA KUPANG) - Leobeti, Orson; Famdale, Rongky Y; Lima, Stofiani Susana (Education For All, 2024)
This research was motivated by problems regarding the implementation of the School Literacy Movement (GLS) program for PKBM Bintang Flobamora students in Kupang City, the school literacy movement had not been implemented in accordance with the existing stages, namely the habituation stage, development stage and learning stage. Apart from these problems, there are also several obstacles that occur in implementing the school literacy movement program, such as, some students do not read but only look at pictures in books. This obstacle is a concern for the school. This research aims to determine the influence of the School Literacy Movement on the reading interest of residents studying at PKBM Bintang Flobamora, Kupang City. This type of research uses a quantitative approach with an ex post facto research design. The population used in this research was PKBM Bintang Flobamora study residents, Kupang City, total sampling, so the sample in this study was 30 study residents. Data collection techniques use questionnaires and documentation. Instrument testing uses validity and reliability. The data analysis technique uses descriptive analysis and prerequisite tests, namely normality test, linearity test, hypothesis test in the form of a simple linear regression test using the terms Ho, accepted and Ha, rejected. Based on data processing from research results with a sample size of 30 residents studying PKBM Bintang Flobamora, Kupang City, it can be concluded that there is a positive and significant influence between the implementation of the School Literacy Movement (GLS) on the reading interest of residents studying PKBM